\[\boxed{\text{807\ (807).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[y = \left\{ \begin{matrix} - 2x + 4,\ \ x > 0 \\ 0,1x - 5,\ \ x \leq 0 \\ \end{matrix} \right.\ \]
\[1)\ y(3) = - 2 \cdot 3 + 4 =\]
\[= - 6 + 4 = - 2\]
\[2)\ y(0,001) = - 2 \cdot 0,001 + 4 =\]
\[= - 0,002 + 4 = 3,998\]
\[3)\ y(0) = 0,1 \cdot 0 - 5 = - 5\]
\[4)\ y( - 8) = 0,1 \cdot ( - 8) - 5 =\]
\[= - 0,8 - 5 = - 5,8\]
\[\boxed{\text{807.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ x³ - 1 = (x - 1)(x^{2} + x + 1)\]
\[2)\ 27 + a³ =\]
\[= (3 + a)(9 - 3a + a^{2})\]
\[3)\ 216 - y^{3} =\]
\[= (6 - y)(36 + 6y + y^{2})\]
\[4)\frac{1}{8}a³ + b³ =\]
\[= \left( \frac{1}{2}a + b \right)\left( \frac{1}{4}a^{2} - \frac{1}{2}ab + b^{2} \right)\]
\[5)\ 0,001m^{3} + 8n^{3} =\]
\[= (0,1m + 2n)\left( 0,01m^{2} - 0,2mn + 4n^{2} \right)\]
\[6)\ a³b³ - c^{3} =\]
\[= (ab - c)(a^{2}b^{2} + abc + c^{2})\]